Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12906-018-2133-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune-enhancing activity of C. militaris fermented with Pediococcus pentosaceus (GRC-ON89A) in CY-induced immunosuppressed model

Abstract: BackgroundCordyceps militaris (C. militaris) is reported to exert various immune-activities. To enhance its activity, we fermented C.militaris with Pediococcus pentosaceus ON89A (GRC-ON89A). In this study, we investigated the immune-enhancing activity GRC-ON89A, using immunosuppressed model.MethodsImmunosuppression was induced by intraperitoneal injection of cyclophosphamide (CY). Each group was orally administered distilled water, GRC-ON89A or GRC, respectively. The phagocytic activities against IgG -opsonize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Pediococcus pentosaceus usually has two important functions in the food field, one is to extent shelf life of food by producing antimicrobial peptides such as bacteriocin or pediocin and others (Kwon et al., 2018; Michalska et al., 2007), and another is to produce protease to improve flavors. Our study displays that P. pentosaceus can produce more extracellular proteins of 51.1k Da due to being induced by S. cerevisiae, which may be consistent with LysM peptidoglycan binding domain proteins based on the molecular weight, can inhibit the adhesion of pathogenic bacteria (Sun, Chen, & Wang, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediococcus pentosaceus usually has two important functions in the food field, one is to extent shelf life of food by producing antimicrobial peptides such as bacteriocin or pediocin and others (Kwon et al., 2018; Michalska et al., 2007), and another is to produce protease to improve flavors. Our study displays that P. pentosaceus can produce more extracellular proteins of 51.1k Da due to being induced by S. cerevisiae, which may be consistent with LysM peptidoglycan binding domain proteins based on the molecular weight, can inhibit the adhesion of pathogenic bacteria (Sun, Chen, & Wang, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Our study also finds that there is relatively high ratio for P. pentosaceus ( P. pentosaceus) in the Chinese Laomian ( P. pentosaceus was detected in eight samples from 13 Chinese traditional Laomian). Pediococcus pentosaceus were commonly found in dairy products (Yu, Chen, Tao, Bo, & Mu, 2015), meat products (Anastasiadou, Papagianni, Filiousis, Ambrosiadis, & Koidis, 2008), and vegetable fermentation products (Xu, Wenshui, Fang, & Xiaohua, 2010), and mainly helpful to the quality, safety, flavor, and shelf life of fermented products (Kwon, Jo, & Park, 2018). But few studies reported action of P. pentosaceus in the dough fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…GRC (5% w / v ) was extracted with distilled water at 105 °C for 2 h and then inoculated with P. pentosaceus ON89A strains. GRC inoculated probiotic strain ON89A were heat-killed at 100 °C for 10 min and sonicated for 3 min (Sonics & Materials, Inc., Newtown, CT, USA) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in our recently published paper, we reported that GRC-ON89A enhanced immune activity and contained higher levels of β-glucan, cordycepin, and short chain fatty acids (SCFAs) than GRC [ 14 ]. SCFAs are known to reduce pro-inflammatory cytokine production [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many biologically active substances have been isolated from C. militaris, such as Cordyceps polysaccharides (CP), Cordycepic acid, cordycepin, mannitol, alkaloids, vitamins B1, B2, and minerals. It was reported that CP has a good protection of the kidneys and liver, lowering blood sugar, antibacterial, anti-inflammatory, anti-tumor, antiarrhythmia, improving immunity and reducing body fatigue [2][3][4]. There are two ways to enhance the value of CP.…”
Section: Introductionmentioning
confidence: 99%